Analysis of the effect of overusing thumbs on smartphone games - Wang, Dong; Tang, Liang; Wu, Huihui; Gu, Dongyun (Journal of international medical research, 2019)
Objective To assess the impact of repetitive movements of the thumb caused by playing a smartphone game continuously for 30 min. Methods This study recruited healthy volunteers. They were instructed to play a game called Subway Surfers, which ran continuously. Subjects played the game for 30 min. The function of the abductor pollicis brevis and extensor pollicis brevis muscles was assessed by surface electromyography and the signals were obtained at 10 min, 20 min and 30 min. The median frequency (MDF) was used as an indicator of muscle fatigue. A visual analogue scale (VAS) was used to assess the subjective discomfort of the volunteers. Results Twelve subjects participated in this study. The MDF of the abductor pollicis brevis and extensor pollicis brevis muscles decreased significantly over the test period. The MDF of the extensor pollicis brevis had decreased significantly by 10 min after the start of the gaming session, while the abductor pollicis brevis had decreased significantly by 20 min. The VAS scores significantly increased after 30 min of continuous gaming. Conclusions This study suggests that playing continuous games on a smartphone might result in chronic muscle injury. Continuous gaming time should be kept below 20 minutes.